2019
DOI: 10.1088/1361-6641/ab337e
|View full text |Cite
|
Sign up to set email alerts
|

Control of complex quantum structures in droplet epitaxy

Abstract: We report the controllable growth of GaAs quantum complexes in droplet molecular-beam epitaxy, and the optical properties of self-assembled AlxGa 1−x As quantum rings embedded in a superlattice. We found that Ga droplets on a GaAs substrate can retain their geometry up to a maximum temperature of 490 • C during post-growth annealing, with an optimal temperature of 320 • C for creating uniform and symmetric droplets. Through controlling only the crystallisation temperature under As 4 in the range of 450 • C to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Meanwhile, the crystallization at edge of droplets induced by As atoms coming from deposition on the droplet surface and decomposition at the interface produces a circular wall surrounding the droplet, as shown by the schematic diagram in figure 1. A lot of experiments show that the diffusion of As atoms are anisotropic and has preferential orientation in [1][2][3][4][5][6][7][8][9][10] or [110] direction [11,15,41]. Therefore, we conjecture that the gaps in hole sidewall are caused by the anisotropic interface diffusion of As atoms.…”
Section: Model and Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Meanwhile, the crystallization at edge of droplets induced by As atoms coming from deposition on the droplet surface and decomposition at the interface produces a circular wall surrounding the droplet, as shown by the schematic diagram in figure 1. A lot of experiments show that the diffusion of As atoms are anisotropic and has preferential orientation in [1][2][3][4][5][6][7][8][9][10] or [110] direction [11,15,41]. Therefore, we conjecture that the gaps in hole sidewall are caused by the anisotropic interface diffusion of As atoms.…”
Section: Model and Resultsmentioning
confidence: 92%
“…For example, recent study has shown that GaAs/AlGaAs or InGaAs/AlGaAs quantum dots obtained by aluminum (Al) droplet etching exhibit ultra-low multi-photon probability and an unprecedented degree of photon pair entanglement [4][5][6][7], as well as entanglement teleportation [8] and entanglement swapping [9]. During droplet epitaxy, liquid droplets initially form on the substrate surface through a III-column element molecular beam, and an As flux is subsequently used for the crystallization with the droplets into the various III-As nanostructures including quantum dots [10,11], quantum rings [12,13] and nanoholes [14][15][16][17] by controlling the intensity of As flux and the crystallization temperature. The formation mechanism of various nanostructures has been studied by some theoretical models which found that the diffusions of III-column atoms and As atoms determined the final geometry of the nanostructures [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the In droplets on the surface of WS 2 follow the Volmer–Weber (VW) growth mode without the presence of a wetting layer (WL). [ 21,22 ] The subsequent step is the droplet crystallization by annealing in the group‐V As element atmosphere at 300 °C for 600 s. During this step, the As atoms impinge on the liquid metal droplets and are dissolved into them to form crystal InAs nanoislands. Figure 1b displays a typical atomic force microscopy (AFM) image of the as‐grown InAs nanoislands/WS 2 heterostructure.…”
Section: Resultsmentioning
confidence: 99%
“…QD arrays with an ultra-low surface density can be formed by the method of droplet epitaxy [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ], which also has additional advantages over the Stranski–Krastanov growth method. Opportunities provided by droplet epitaxy include the possibility for QD growth without a wetting layer [ 10 , 15 , 16 , 17 ], the fabrication of nanostructures and complexes of nanostructures of various shapes [ 11 , 14 , 17 , 18 , 19 , 20 , 21 ] and QD growth in lattice-matched material systems, such as GaAs/AlGaAs, etc. [ 12 , 16 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%